Robotska vadba pri pacientu s poškodbo brahialnega pleteža – prikaz primera - Zgonc, Ema (Rehabilitacija (Ljubljana), 2022)
Background: A brachial plexus injury causes upper limb imobility, reduced sensitivity and causes pain sensation loss in the upper limb, resulting in difficulties performing basic and instrumental activities of daily living. The Armeo® Spring robotic device is an adjustable system for the upper limb. We present an example of an occupational therapy treatment in a patient with brachial plexus injury and the effects of robotic therapy after a longer period following the injury. Methods: The subject was a 31-year-old motorcyclist who sustained motor nerve impairment in the area from C4 to C6 on the right side. He also reported tingling and neuropathic pain in his right shoulder and upper arm. For assessment, we used the Canadian Occupational Performance Measure (COPM), dynamometer, the short form of the Disabilities of the Arm, Shoulder, and Hand outcome measure (QuickDASH), the Action Research Arm Test (ARAT), and range-of-motion measurements of the Armeo® Spring device. The patient was involved in occupational and robotic therapy. Results: According to COPM, the average activity performance score was 2 in the beginning and 5.5 at the end of rehabilitation. Hand grip strength improved. The QuickDASH measurements increased by 3 points. At the beginning, the ARAT assessment showed deviations in all areas, but later only in pinch grip and gross movements. According to measurements on the Armeo® Spring, the range of motion improved. Conclusion: The results show that therapy on a robotic device may be a useful complementary method in the rehabilitation of patients after brachial plexus injury.
Keywords: Brachial Plexus; delovna terapija; injuries; occupational therapy; rehabilitacija; rehabilitation; Robotics; robotika